You are on page 1of 4

SECTION 2.6

LIMITS AT INFINITY; HORIZONTAL ASYMPTOTES

1

|||| 2.6 Limits at Infinity; Horizontal Asymptotes

A

1–8 |||| Evaluate the limit and justify each step by indicating the appropriate properties of limits.

1.

3.

5.

7.

lim

x l

lim

x l

1

xsx

x 4

x 2 2x 5

lim

x l

1 x 2 x 1 2x 2 3x

lim

x l

1

3 sx

9–26 |||| Find the limit.

r 4 r 2 1
9.
lim
r
l
r 5 r 3 r
s1 4x 2
11.
lim
x
l
4 x
1
sx
13.
lim
x
l
1
sx

2.

4.

6.

8.

10.

12.

14.

lim

x l

lim

t l

lim

x l

lim

x l

5 2x

3 x

7t 3 4t

2t 3 t 2 3

2x 2 1

x 8x 2

sin 2 x

x 2

lim

t l

lim

x l

6t 2 5t

1 t 2t 3

sx 2 4x

4x 1

lim (sx

2 3x 1 x)

x l

S

15.

16.

17.

19.

21.

23.

25.

lim (sx 2 1 sx 2 1)

x l

lim (s1 x sx)

x l

(s 3

lim

x

l

1 x s

3

x)

lim (x sx)

x

l

lim

x l

x 7 1 x 6 1

lim x 2 x 4

x l

lim

x l

sx 3

x 3

18.

20.

22.

24.

26.

lim

x l

lim

x l

x 1 x)

(sx

2

x

3

5x

2

lim

x l

lim

x l

lim

x l

e x 2

x 3 1

x 4 1

x

sx 1

27. Guess the value of the limit

5

x 2

for

lim x 2 sin

x l

2 sin 5 x 2

by evaluating

9, 10, 20, 50, and 100. Then conﬁrm your guess by evaluating

this limit exactly.

f x x

x 1

, 2, 3, 4, 5, 6, 7, 8,

2

SECTION 2.6

LIMITS AT INFINITY; HORIZONTAL ASYMPTOTES

E

1.

8.

14.

20.

26.

0

0

3

2

2.

9.

2

0

15.

0

21.

27.

5

3.

10.

16.

0

3

0

22.

0

4.

7

2

11.

17.

2

0

23.

5.

1

6

12.

18.

6.

1

4

1

2

24.

1

2

0

7.

13.

0

1

19.

25.

0

S

SECTION 2.6 LIMITS AT INFINITY; HORIZONTAL ASYMPTOTES 3

Solutions

1. lim

x

→∞

2. lim

x

→∞

1

x x = lim

x

→∞

1

/ 2 = 0 by Theorem 5.

x

3

5+2x

3 x

= lim

x

→∞

5

x

+ 2

x →∞

lim

5

x + 2

(5)

=

3

x

1

x →∞

lim

3

x

1

(1,2,3)

=

1

 5 lim + lim →∞ 2 5 (0) + 2 x →∞ x x 3 lim 1 − lim = 3 (0) − 1

x

→∞

x

x

→∞ 1

= 2 by (9) and Theorem 5.

3. lim

4.

x

→∞

lim

t

→∞

x + 4 x 2 2x

+

5 = lim

x

→∞

1

x + x 2

4

1

2

x + x 2

5

(5)

=

→∞

lim

x

1

x + x 4 2

lim →∞ 1

x

2

x + x 5 2

(1,2,3)

=

1

lim x + 4 lim

x

→∞

x

→∞

1

x

2

1 2 lim

lim

x

x →∞

1

x + 5 lim

x →∞

1

x

2

=

0 + 4 (0) 1 2 (0) +

5 (0) = 0 by (9) and Theorem 5.

7t 3 + 4t

2t 3 t 2

+

3 = lim

t

→∞

7 +

4

t

2

2

1

t

3

+ t 3

(5,1,2,3)

=

t

lim 7 + 4

lim

t

→∞

1

t

2

t 2 lim

lim

t

→∞

1

t

+ 3 lim

t

→∞

1

t

3

=

7 + 4 (0) 2 0 + 3 (0) = 7

2

by (9) and Theorem 5.

5.

x

lim

→−∞

 1 − 1 2 x + 1 x x →−∞ 1 + 2 2 x − 3 x lim 1 − 1 x lim →−∞ 2 x + 1 x →−∞ x lim 1 + 2 x lim →−∞ 2 x − 3 x →−∞ x

(1 x) (2 + x)

(1 + 2x) (2 3x) = lim

=

(5,4,1,2,7)

=

(0 1) (0 + 1)

= 1

6

(0 + 2) (0 3)

x →∞

6. lim

2x 2 1

x + 8x 2

1 / 2 (11)

=

lim

x →∞

2 1

x

2

1

x + 8

(5,1,2)

=

lim 2 lim

x

x

→∞

1

x

2

lim

x →∞

1

x + lim

x

→∞ 8

1

= 1

2 by (9) and Theorem 5.

1

/ 2

/ 2

= 2 0

0+8 1 / 2

7.

lim

x

→∞

1

3 + x = lim

x

→∞

1/ x

(3/ x )+1

(5,1,3)

=

lim (1/ x )

x

(1/ x ) + lim

3 lim

x

x

→∞ 1 =

0

3 (0) + 1

= 0 by Theorem 5 with r = 1 2 .

Or: Note that 0 <

Theorem.

1

1

3 + x <

x and use the Squeeze

8.

sin 2 x

Since 0 sin 2 x 1, we have 0

x

1 2 for all

x

2

x

0=0 and

= 0. By (9) and Theorem 5 we have lim

x

lim

x

→∞

lim

x

→∞

1

= 0. So, by the Squeeze Theorem,

x

sin 2 x

2

x

2

= 0.

9.

lim

r

→∞

1

1

1

r 4 r 2 + 1

r 5 + r 3

r

r 3 + r 5

r = lim

r

→∞

1 + 1

1

r

2

1

4

r

1

r

3

lim r lim

r

→∞

r

→∞

+ lim

r

→∞

1

r

5

=

1 + lim

lim

r

r

→∞

1

r

2

lim

r

→∞

1

r

4

= 0 0+0

1+0 0

= 0

10. lim

t

→−∞

6t 2 + 5t

(1 t) (2t 3) =

lim

t

→−∞

6t 2 + 5t

2t 2 + 5t 3

= lim

t

→−∞

6+5/t

2+5/t 3/t 2

=

t

6 + 5 lim

lim

t

(1/t)

t

(2) + 5 lim

lim

t

(1/t) 3 lim

t

(1/t 2 )

=

6 + 5 (0)

2 + 5 (0) 3 (0)

= 3

11. lim

x

→∞

1+4x 2

4 + x

= lim

x

→∞

(1/x 2 )+4 = 0+4

(4/x )+1

0+1 = 2

4

SECTION 2.6 LIMITS AT INFINITY; HORIZONTAL ASYMPTOTES

12.

x

lim

→−∞

x 2 + 4x

4x + 1

= lim

x

→−∞

= 1

4

1+4/x = 1+0

4+1 /x

4+0

Note: In dividing numerator and denominator by x, we used

13.

the fact that for x < 0, x = x 2 .

lim

x

→∞

1 + − √ x x = lim
1

x

→∞

(1/ x ) 1

(1/ x )+1 = 0 1

0+1 = 1

14. lim

x

x 2 + 3x + 1 x

=

x 2 + 3x + 1 x x 2 + 3x +1+ x

x 2 + 3x +1+ x

lim

x

= lim

=

x

→∞

lim

x →∞

x 2 + 3x + 1 x 2

x 2 + 3x +1+ x 3 x + 1

x 2 + 3x +1+ x

= lim

x →∞

3+1/x

1 + (3/x ) + (1/x 2 )+1

=

3+0

1+3 · 0+0+1 = 2 3

15. lim

x

x 2 + 1 x 2 1

√ x 2 +1+ √ x 2 − 1

x 2 +1+ x 2 1

x 2 + 1 x 2 1

= lim

x

= lim

x →∞

= lim

x

→∞

x 2 + 1 x 2 1

x 2 +1+ x 2 1

2

x 2 +1+ x 2 1

= lim

x

→∞

2/x

1 + (1/x 2 ) + 1 (1/ x 2 )

0

= 1+0+ 1 0 = 0

18. x x 2 + x +1+ x

lim

= lim x 2 + x +1+ x

x

= lim

x

→−∞

x + 1

x 2 + x + 1 x

x

x 2 + x + 1 x

2

+ x + 1 x

= lim

x

→−∞

1 + (1/x)

1 + (1/x ) + (1/x 2 ) 1

=

1+0

1+0+0 1 = 2 1

19.

(x + x ) = since x → ∞ and x → ∞.

lim

x

20. x lim x 3 5x 2 = −∞ since x 3 → −∞ and

5 x 2 → −∞ as x → −∞.

Or: lim

x

x 3

5x 2 = lim x 2 (x 5) = −∞ since

x

x 2 → ∞ and x 5 → −∞.

x 7 1

1 1 x 7

21. x 6 +

lim

x →∞

1

x

= lim

x →∞

(1/x ) +

x + x 1

1

(1/x 7 ) = since

1

1 7 1 while

7

0 + as x → ∞.

Or: Divide numerator and denominator by x 6 instead of x 7 .

22. As x → ∞ , x 2 → ∞ and x 2 → −∞ . Thus,

e x 2 = lim

lim

x

t

→−∞ e t = 0.

23. lim

x

x 2

x 4 = lim

x

x 2 1 x 2 = −∞ since x 2 → ∞

and 1 x 2 → −∞.

24.

25.

26.

x 3 1

lim x 4 + 1 = lim

x →∞

x

→∞

(1/x ) 1 x 4

= 0 0

1 + (1/x 4 )

1+0 = 0

lim

x →∞

lim

x →∞

x + 3

=

lim

x + 3

x

x

→∞

x

1 = lim

x

→∞

(1/ x ) + (3/x) = 0+0

1+3/x

1+0 = 0

x

/ x

x 1 / x

16. lim

x

1 + x x

x

=

lim

x

→∞

1 1/x =

1 + x x

= lim

x

=

lim

x

→∞

(1 + x) x

1 + x + √ x

1 + x + x

since x → ∞ and 1 1/x 1.

1 Or: Divide numerator and denominator by x instead of x.

27. If f

(x) = x 2 sin 5 x 2 , then a calculator gives the

1 + x + x = lim 1 + x + x

x

→∞

=

lim

x

→∞

1/ x

0

(1/x )+1+1

=

0+1+1 = 0

17. Using a 3 b 3 = (a b) a 2 + ab + b 2 with a =

and b = x, we have

3

→∞

lim

x

1 + x x

3

3

1 + x

3

=

=

lim

x →∞

lim

x

→∞

(1 + x) x

(1 + x) 2 / 3 + (1 + x) 1 / 3 x 1 /3 + x 2 /3

1

(1 + x) 2 / 3 + (1 + x) 1 / 3 x 1 /3 + x 2 /3 = 0

following approximate values: f (1) = 0.95892,

 f (2) = 3.79594, f (3) = 4.74674, f (4) = 4.91902, f (5) = 4.96673, f (6) = 4.98394, f (7) = 4.99133, f (8) = 4.99492, f (9) = 4.99683, f (10) = 4.99792, f (20) = 4.99987, f (50) = 4.999997 , f (100) = 4.9999998. It appears that

lim x 2 sin 5 x 2 = 5.
x

Proof: Let t =

x 1 2 . Then as x

→ ∞, t 0 and

0

x 2 sin 5 2 = lim

lim

x

x

t

1

t

sin 5t = 5 lim

t

0

sin 5t

5t

= 5.